Crosslinking of Hardwood Lignin with Citric Acid for Sustainable Wood Adhesives (Journal of Research Updates in Polymer Science, 2025)
The toxicity of petroleum-based crosslinkers raises health and environmental concerns, prompting interest in bio-based alternatives. This study reports the facile crosslinking of hardwood lignin (HWL) with citric acid (CA) as a bio-crosslinker for application as a lignin-based wood adhesive. HWL is characterized by GPC and DSC to determine its molecular weight and glass transition temperature, respectively. The successful crosslinking and esterification reactions of the HWL-CA-based resin are confirmed by the exothermic peaks observed in the DSC thermogram and by FT-IR analysis. The HWL-based adhesives with various proportions of CA meet the Korean standard shear strength requirement of 0.60 MPa, with 12% CA (HWL-CA12) giving the maximum value of 1.07 MPa. The successful surface modification of the veneer pre-treatment with CA is also confirmed by FT-IR analysis. Although the adhesive strength of the HWL-CA12 is decreased on the pre-treated veneer relative to the untreated veneer, it remains above the standard requirement on the veneers that were treated with 10% and 15% of CA. These findings demonstrate the potential of CA-crosslinked lignin as a sustainable alternative to petroleum-based wood adhesives.